Mineralogical investigation of the Nepheline syenite Franspoort, South Africa for beneficiation - Merkle, R.K.W. (Roland Karl Willi), 1954- (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2010.